2014
DOI: 10.1080/10942912.2014.923440
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Milk Chocolates as Influenced by Milk Powder Type, Emulsifier, and Cocoa Butter Equivalent Additions

Abstract: The research examines the influences of different emulsifiers (lecithin, CITREM LR10-both individually and combined with polyglycerol polyricinoleate, and CITREM 2in1) and cocoa butter equivalent additions on the rheological properties of milk chocolates produced using spray or roller-dried milk. The substitution of lecithin with other emulsifiers caused an increase in the Casson plastic viscosity (µ CA ), as well as a decrease in the Casson yield stress (τ CA ) in milk chocolates containing roller-dried milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
(16 reference statements)
2
10
0
1
Order By: Relevance
“…Yield stress values were obtained from shear rate versus shear stress data and are shown in behavior. This behavior observed in SMC samples has also been reported in another study as a result of replacing roller-dried milk powder with spray-dried milk powder (Ačkar et al, 2015).…”
Section: Yield Stresssupporting
confidence: 85%
“…Yield stress values were obtained from shear rate versus shear stress data and are shown in behavior. This behavior observed in SMC samples has also been reported in another study as a result of replacing roller-dried milk powder with spray-dried milk powder (Ačkar et al, 2015).…”
Section: Yield Stresssupporting
confidence: 85%
“…Contrariwise, Sun and Gunasekaran (2009) and Xi et al (2019) found that the Power-law model adequately described the flow behaviour of 2% (w/w) WPIstabilized emulsions. The Casson fluid model is commonly used to describe the behaviour of melted chocolate and chocolate milk, but it might also be used to cream/paste, liquid milk, and ice cream (Ačkar et al, 2015;Cropotova et al, 2017;Poursani et al, 2020). The Herschel-Bulkley model is a generalized model for describing the non-Newtonian behaviour of various fluid foods with shear-thinning properties (Tadros, 2013).…”
Section: Flow Behaviour Of Emulsionsmentioning
confidence: 99%
“…Extensive studies have been conducted to exploit novel trans-free fats and assess their potential performance in various food products such as margarines (Hu, Xu, & Yu, 2017;Lakum & Sonwai, 2018;Li et al, 2018b;Ornla-Ied, Sonwai, & Lertthirasuntorn, 2016;Pande, Akoh, & Shewfelt, 2012), shortenings (Saghafi et al, 2018;Xu et al, 2018), as well as fat-frozen special fats (Zhu et al, 2019;Zhu et al, 2018b;Zhu et al, 2017). CBEs, as the name indicates, have been primarily applied to partially substitute cocoa butter in chocolate products, such as dark chocolates (De Clercq et al, 2017;Jin, Jin, Wang, & Akoh, 2019;Souza & Block, 2018), white chocolates (Bahari & Akoh, 2018b), and milk chocolates (Ackar et al, 2015). Similarly, HMFSs particularly those enriched in PUFAs has been widely applied in emulsion-based infant formula (Li, Sabir, Baeshen, & Akoh, 2015b;Zou & Akoh, 2015a.…”
Section: Potential Food Applications Of Slsmentioning
confidence: 99%